MENINGKATKAN EFEKTIVITAS KERJA KARYAWAN MELALUI MOTIVASI KERJA SEBAGAI VARIABEL INTERVENING PADA PT ALBA BAJA - Safitri Putri Derajat; Abdul Wahid Alfarizi (GEMILANG: Jurnal Manajemen dan Strategi Bisnis, 2022)
Not achieving work targets and work results according to the Key Performance Indicator (KPI) indicates a problem with employee effectiveness. A comfortable work environment and maximum work supervision are needed to be able to increase employee work effectiveness which is strengthened by work motivation. This study aims to determine the effect of work environment and work supervision on employee effectiveness through work motivation as an intervening variable. The study consisted of four variables, namely work environment and supervision as independent variables, work effectiveness as the dependent variable and work motivation as intervening variables. The object of research is the employees of PT Alba Baja. This study used a quantitative approach with data collection techniques in the form of filling out questionnaires as measured by an interval rating scale of 1-10. Samples were taken as many as 95 respondents with stratified random sampling technique. Research data were analyzed using Structural Equation Modeling (SEM) which was processed with SmartPLS version 2.3.m3. Based on the results of hypothesis testing, it can be concluded (1) the work environment has a positive and significant effect on work effectiveness, where the more conducive the work environment, the higher the employee work effectiveness; (2) Supervision has a positive and significant effect on work effectiveness, where the higher the supervision carried out, the higher the employee work effectiveness; (3) The work environment has no effect on work motivation, meaning that high employee motivation is not influenced by a conducive work environment; (4) Supervision does not affect work motivation, where high supervision from management does not affect employee motivation; and (5) work motivation does not affect work effectiveness, meaning that high employee work motivation does not affect employee work effectiveness.